Od načrta skrbi in programa oskrbe do osebnega načrtovanja in izvajanja storitev - Videmšek, Petra (Socialno delo, 2018)
The method of personal planning has been present in Slovenia since the mid-1990s and introduced the paradigmatic changes in social work that are reflected in the implementation of the users' perspective in the process of help. The paper presents the use of the method since its initial introduction in the field of handicap to the present day, when the method is, for institutional carers of older people, even formally defined in legal regulations. Some of the most evident changes are presented, from the change of naming the method itself, to the influence of conceptual changes on the role of people with personal experience of distress in the implementation of the method and its recording. Based on the analysis of the individual plans, the fundamental advantages of using the method in social work are shown, and the attention is drawn to the traps presented to experts, especially in the institutional environment in which they implement the method. For social work, it is important to constantly analyze the implementation of the method and to evaluate the attainment of compliance of the objectives of the method with the concepts of social work.
Keywords: social work; socialno delo; empowerment; krepitev moči; uporabniška perspektiva; user perspective; writing; zapisovanje; deinstitutionalisation; dezinstitucionalizacija; individualisation; individualizacija